Digitalization of Bureaucracy and Public Service Delivery in Aceh: Integrating Islamic Sharia Principles - Muazzinah, Muazzinah; Khalil, Zakki Fuad; Zamharira, Cut; Ulfa, Khalida; Said, Mohd Zulhafiz (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
The rapid advancement of information technology over the past two decades has significantly transformed societal dynamics, presenting new challenges and opportunities for public administration. The digital era, characterized by unprecedented access to information and accelerated technological and scientific innovation, has compelled governments to continuously adapt their bureaucratic systems to deliver public services that are effective, efficient, and responsive to citizens’ needs. This study examines the digitalization of bureaucracy and public services in Aceh Province from an Islamic Sharia perspective. The research employs qualitative data analysis using NVivo 12 Plus, specifically utilizing the crosstab and NCapture features to identify patterns and relationships within the data. The findings indicate that the digitalization of bureaucracy and public services in Aceh has been largely successful, with technological innovation emerging as the most influential factor. Additional key determinants include strategic planning, human resource capacity, leadership, and community participation. Nevertheless, the effective implementation of digital public services requires strict adherence to fundamental public administration principles, particularly accountability, transparency, affordability, and responsiveness. From an Islamic Sharia perspective, digitalization is expected to prioritize public convenience and social benefit (maslahah) while ensuring justice and equality for all members of society. These findings highlight the importance of aligning technological innovation with ethical and normative values in the governance of digital public services